Índice Revista INNOVAR, números 1-10 (1997)
Índice de la revista: No. 1, 1991; No. 2,1992; No. 3, 1993; No. 4, julio-diciembre de 1994; No. 5, enero-junio de 1995; No. 6, julio - diciembre de 1995; No. 7, enero - junio de 1996; No. 8, julio - diciembre de 1996; No. 9, enero - junio de 1997; No. 10, julio - diciembre de 1997.